Seamless Interconnection for Universal Services. Global Telecommunications Conference. GLOBECOM'99. (Cat. No.99CH37042)
DOI: 10.1109/glocom.1999.831628
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel RS/convolutional concatenated coded QAM for hybrid IBOC-AM broadcasting

Abstract: Abstract-Bandwidth efficient modulation schemes using Reed-Solomon (RS) codes are proposed for Hybrid In-Band-On-Channel (IBOC) systems that broadcast digital audio signals simultaneously with analog Amplitude Modulation (AM) programs in the AM band. Since both the power and bandwidth allocated for digital audio transmission are limited in this application, the system cannot afford to add enough redundancy for error control using conventional concatenated coding schemes. We show that by using multilevel RS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…We evaluate methods of applying outer CRC codes to PAC, an audio coder that has variable frame length. Similar experiments to these should also be repeated for other outer codes such as Reed-Solomon codes, which are preferred for digital audio broadcasting systems in the AM band with multilevel modulation [4], [26], [27]. We conclude that the variable length outer CRC code integrated with the PAC audio coder is a more effective method of applying the outer CRC code.…”
Section: B Variable Crc Resultsmentioning
confidence: 99%
“…We evaluate methods of applying outer CRC codes to PAC, an audio coder that has variable frame length. Similar experiments to these should also be repeated for other outer codes such as Reed-Solomon codes, which are preferred for digital audio broadcasting systems in the AM band with multilevel modulation [4], [26], [27]. We conclude that the variable length outer CRC code integrated with the PAC audio coder is a more effective method of applying the outer CRC code.…”
Section: B Variable Crc Resultsmentioning
confidence: 99%
“…The paper showed that, by applying concatenated codes to only the lowest level of the multilevel scheme, an additional 0.8 dB of coding gain can be obtained, compared to the multilevel RS coded QAM scheme [103].…”
Section: Fec and Modulation Schemesmentioning
confidence: 99%
“…24 are concatenated outer RS codes and inner trellis-coded modulation (TCM) based on 16-, 32-, or even 64-QAM constellations [72], [96]. Due to the limited bandwidth available for hybrid IBOC-AM systems, alternate FEC schemes have also been explored [97], and the results are summarized in Section VI-C.…”
Section: A 30-khz Hybrid Iboc-am Systemmentioning
confidence: 99%
See 2 more Smart Citations